2007
DOI: 10.1590/s1516-635x2007000100006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the supplementation of vitamins and organic minerals on the performance of broilers under heat stress

Abstract: The objective of this experiment was to evaluate the effect of diet supplementation with vitamins C and E and organic minerals Zn and Se on the performance of 1 to 35 day-old broilers from, kept under cyclic heat stress (25 to 32ºC). Four levels of vitamin-mineral supplementation were used (T1-control diet (60/30 IU of vit E for starter and growing diet, respectively, zero vit. C, 80 ppm of inorganic Zn, 0.3 ppm of inorganic Se); T2-control diet + 100 UI vit E and 300 ppm vit C/kg; T3-control diet + 40 ppm Zn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 18 publications
3
16
0
6
Order By: Relevance
“…The positive effect of zinc supplementation on feed conversion may be attributed to the improvement in nutrient digestibility and efficiency of their use (Lagana et al, 2007 andSahin et al, 2009) and therefore improve feed conversion ratio. Zinc has a protective role on pancreatic tissue against oxidative damage; it may therefore help the pancreas to function properly, including the secretions of digestive enzymes, thus improving the digestibility of nutrients and consequently, performance.…”
Section: Resultsmentioning
confidence: 99%
“…The positive effect of zinc supplementation on feed conversion may be attributed to the improvement in nutrient digestibility and efficiency of their use (Lagana et al, 2007 andSahin et al, 2009) and therefore improve feed conversion ratio. Zinc has a protective role on pancreatic tissue against oxidative damage; it may therefore help the pancreas to function properly, including the secretions of digestive enzymes, thus improving the digestibility of nutrients and consequently, performance.…”
Section: Resultsmentioning
confidence: 99%
“…Vitamins and trace minerals such as carotenoid, vitamin E, vitamin C, selenium and zinc showed to enhance immunity by maintaining the functional and structural integrity of important immune cells (Chew 1995;Muir et al 2002;Singh et al 2006;Lagana et al 2007). On the contrary, our results indicated that irrespective of duration, withdrawal of VIT and TRM premixes did not influence antibody response against ND vaccinations when compared to controls (Table 3).…”
Section: Immune Responsementioning
confidence: 99%
“…al., 2001;Singh, et.al., 2006;Laganá et. al., 2007) e concorda com os resultados observados no presente estudo.…”
Section: Desempenho Geralunclassified